Legal review of land tenure in the Ambal Urut Sewu Area, Kebumen Regency, Central Java Province by the TNI AD Kodam IV/Diponegoro - Rahmatullah Rahmatullah (Dynamics of Politics and Democracy, 2023)
Purpose: The agrarian conflict that occurred in the Ambal Urut Sewu area, Kebumen Regency, Central Java Province between the community and the Indonesian Army, Kodam IV/Diponegoro has not been resolved even though the National Land Agency (BPN) has issued a Certificate of Land Use Rights (SHP) to the Indonesian Army. The community assumes that the land is a hereditary property right based on proof of ownership Letter C. In addition to having documents proving that the land is state land resulting from the transfer of armed forces belonging to the Dutch colonial government in Indonesia during the colonial period, the Indonesian Army has also strengthened this by issuing a SHP for land in the area for the Indonesian Army. This stagnant condition underlies the research carried out with the aim of obtaining answers about the legality of land ownership and management, and how to resolve the duplication of control over part of the Indonesian Army training land with the surrounding community. Research/methodology: This research uses a qualitative research method through a descriptive analytical deductive approach with data collection through library research, field observations, and in-depth interviews. Data processing from data transcription, and data organization are analyzed until patterns, themes, and concepts can be identified. Results: Legally, the TNI AD Kodam IV/Diponegoro has the legality to use or utilize land in the Ambal Urut Sewu Area based on the SHP, and the letter of the Directorate General of State Assets of the Ministry of Finance of the Republic of Indonesia Number: S-825/KN/2011 dated April 29, 2011 which confirms that the land in the Ambal Urut Sewu Area is an asset of the TNI AD with Registration Number: 30709034 ownership year 1949 from the handover of the KNIL on July 25, 1950 with an area of ??1,150 Ha. Alternative resolution through mediation is a resolution that must be taken by both parties.